Các yếu tố ảnh hưởng đến áp dụng quản lý chuỗi cung ứng xanh của các doanh nghiệp nhỏ và vừa: Nghiên cứu tại Hà Nội, Quảng Ninh và Thành phố Hồ Chí Minh - Bùi Duy , Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The objective of this study is to identify factors affecting the application of green supply chain management by small and medium-sized enterprises in some provinces and cities of Vietnam. Research data was collected from 259 small and medium-sized enterprises in Hanoi, Quang Ninh, and Ho Chi Minh city. Data analysis methods applied in this study include testing the reliability of the scale, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and linear structural modeling (SEM). Research results show that Government Support, Environmental Regulations, Strategic Direction, and Business Resources are factors that have positive impacts on the application of green supply chain management. On that basis, the study proposes recommendations to promote green initiatives and practices in the supply chain of small and medium-sized enterprises.
Keywords: Green Supply Chain; Strategic Direction; Government Support; Business Resources; Environmental Regulations